Tissue- and Condition-Specific Isoforms of Mammalian Cytochrome c Oxidase Subunits: From Function to Human Disease. (16th May 2017) - Sinkler, Christopher A.; Kalpage, Hasini; Shay, Joseph; Lee, Icksoo; Malek, Moh H.; Grossman, Lawrence I.; Hüttemann, Maik
Abstract : Cytochrome c oxidase (COX) is the terminal enzyme of the electron transport chain and catalyzes the transfer of electrons from cytochrome c to oxygen. COX consists of 14 subunits, three and eleven encoded, respectively, by the mitochondrial and nuclear DNA. Tissue- and condition-specific isoforms have only been reported for COX but not for the other oxidative phosphorylation complexes, suggesting a fundamental requirement to fine-tune and regulate the essentially irreversible reaction catalyzed by COX. This article briefly discusses the assembly of COX in mammals and then reviews the functions of the six nuclear-encoded COX subunits that are expressed as isoforms in specialized tissues including those of the liver, heart and skeletal muscle, lung, and testes: COX IV-1, COX IV-2, NDUFA4, NDUFA4L2, COX VIaL, COX VIaH, COX VIb-1, COX VIb-2, COX VIIaH, COX VIIaL, COX VIIaR, COX VIIIH/L, and COX VIII-3. We propose a model in which the isoforms mediate the interconnected regulation of COX by (1) adjusting basal enzyme activity to mitochondrial capacity of a given tissue; (2) allosteric regulation to adjust energy production to need; (3) altering proton pumping efficiency under certain conditions, contributing to thermogenesis; (4) providing a platform for tissue-specific signaling; (5) stabilizing the COX dimer; and (6) modulating supercomplex formation.